EFEK LAMA PERENDAMAN TERHADAP PERKECAMBAHAN BENIH ROSELA (Hibiscus sabdariffa L.) - Suhendra, Dede (JURNAL AGROPLASMA, 2019)
Rosela (Hibiscus sabdariffa L.) is a medicinal plant. Rosela has a chemical compound that can provide many benefits. Efficacy of rosella to prevent disease, treat disorders of various diseases with gossiptin anthocyanin content and gluciside hibiscin contained in it. This research was conducted at the Laboratory of College of Agricultural Sciences of Labuhan Batu University Foundation, North Sumatera Province. This research was started in March 2017. This research used Non-Factorial Randomized Block Design (RAK) with the harvesting period (P) P0: Control, P1: 1, Clock P2: 2 Hours, P3: 3 Hours P4: 4 Hours P5: 5 Hours P6: 6 Hours P: 7 Hours. The highest rate of germination was found in P7 treatment of 3.22 days. The highest normal germination percentage was found in P5 and P7 treatment of 66.67%. Than highest abnormal germination percentege was found in P3, P4 and P6 treatment of 33.33 %. Keywords : Rosela, Old Immersion